A cortical bone phantom with accurate permittivity at 100 kHz. (18th January 2016) - Prinable, J B; Barry, T; McEwan, A; Jones, P; Carter, P
Abstract: Physical phantoms in conjunction with an electrical impedance system may offer a method to analyse current spread through the cochlea. In this paper, a preliminary attempt was made to make a phantom with permittivity and conductivity values similar to that of the temporal bone. Since there was no in vivo AC measurements recorded in the literature, an analog of cortical bone was created. The phantom material was found to have higher conductivity than that of cortical bone between the frequency range of interest (10 kHz–1 MHz) when 0.2 g of graphite was present in the phantom. However, the permittivity could be matched at set frequencies for different mixes. A phantom could be created that had the permittivity within 10% at a set frequency if the data points are interpolated. This may allow the construction of a cortical bone phantom at other frequencies of interest.